Multidisciplinary exhibit design in a Science Centre: a participatory action research approach. Issue 4 (8th August 2018) - Rudman, Hannah; Bailey-Ross, Claire; Kendal, Jeremy; Mursic, Zarja; Lloyd, Andy; Ross, Bethan; Kendal, Rachel L.
Abstract: In this paper we highlight the issues and opportunities of a participatory action research (PAR) and co-design project, currently being undertaken as engaged research between academics at Durham University and practitioners at the UK's International Centre for Life in Newcastle-Upon-Tyne (CfL; see creativescienceatlife.com for more information and developments). The focus is on the use of PAR to enable university researchers and Science Centre professionals to co-design Informal Science Learning exhibits that enhance creativity and innovation in young people. We define the principles of PAR and explore reasons for adopting the approach. An account is provided of the iterative co-design and piloting of a novel exhibit within a new exhibition space at the CfL. Reflections collated independently by the practitioners and the academics involved highlighting the development of ideas and insights over the course of the PAR process. We discuss how PAR enabled effective engagement with and creation of enriched knowledge, and innovation, in both the academy and science-learning professionals. The added value of PAR and co-production to our project aligns with current calls for a redefining of how societal impact of academic research is considered.